PANTUN PERNIKAHAN MELAYU KAPUAS HULU : KAJIAN LINGUISTIK FUNGSIONAL SISTEMIK - SELLY PURWATI; AHADI SULISSUSIAWAN; AHMAD RABI'UL MUZZAMMIL (Universitas Tanjungpura, 2022)
This research is motivated by the contribution of knowledge in culture and language, especially in the Kapuas Hulu Malay wedding rhyme tradition. The result of this research is an analysis of marriage rhymes which are divided into rhyme themes, rema rhymes and types of rhymes based on the study of Systemic Functional Linguistics. The data source for this research is a summary of the Kapuas Hulu Malay wedding rhyme which was made by three indigenous people from Kapuas Hulu. The three people are Muhammad Kasim, Abdul Ma'an and Mahmudin. The data collection technique was carried out by taking data from books, analyzed and recorded based on their grouping with the study of Systemic Functional Lingustics. The results of this study were compiled through data collection in the Kapuas Hulu Malay wedding rhymes, 45 wedding rhymes were selected. The data includes the theme of topical rhymes as many as 14 wedding poems, interpersonal themes as many as 11 wedding poems and textual themes as many as 20 wedding poems.